2015
DOI: 10.1080/02699931.2015.1020049
|View full text |Cite|
|
Sign up to set email alerts
|

Will you touch a dirty diaper? Attitudes towards disgust and behaviour

Abstract: Individuals differ in their willingness to engage with disgusting stimuli (e.g., dirty diapers). We propose that such differences are associated with attitudes towards disgust. Specifically, we predicted that people with less negative attitudes towards disgust (i.e., those who evaluate disgust less negatively) would be more willing to engage with disgusting stimuli. We asked participants to engage with disgusting stimuli in the laboratory and used two measures that assess behavioural and affective or cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…However, previous work has also produced evidence for situation selection that reflects a contra-hedonic preference 8 or found no difference in situation selection based on different valence categories 9 , 10 , 12 , 38 . The presence of hedonic and contra-hedonic situation selection across studies could be driven by factors such as participants’ age 11 , attitude towards emotions 39 , their emotional goals 40 43 , or motivation 44 , social context of ER 40 , as well as levels of arousal 9 , interest 9 , 45 , or attractiveness of the stimuli 46 . Why we observed the hedonic pattern in this particular context is unclear; efforts to understand the mixed nature of findings in this domain deserve attention in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work has also produced evidence for situation selection that reflects a contra-hedonic preference 8 or found no difference in situation selection based on different valence categories 9 , 10 , 12 , 38 . The presence of hedonic and contra-hedonic situation selection across studies could be driven by factors such as participants’ age 11 , attitude towards emotions 39 , their emotional goals 40 43 , or motivation 44 , social context of ER 40 , as well as levels of arousal 9 , interest 9 , 45 , or attractiveness of the stimuli 46 . Why we observed the hedonic pattern in this particular context is unclear; efforts to understand the mixed nature of findings in this domain deserve attention in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have found positive relationships between people's attitudes towards a particular emotion and whether they choose to strive for, or engage with, that emotion (Markovitch et al, 2016(Markovitch et al, , 2017. Emotion regulation choice has also been found to be associated with people's self-reported and/or externally manipulated beliefs about particular emotions, such including how much control they believe they have over their emotions (e.g.…”
Section: Individual Determinantsmentioning
confidence: 99%
“…Chen et al, 2007), attitudes (e.g. Markovitch et al, 2016Markovitch et al, , 2017, and beliefs (e.g. Tamir & Ford, 2012a, 2012b.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…Some people are more inclined to make appraisals that other people are accountable for negative outcomes and these people are more prone to anger (Kuppens, Van Mechelen, & Rijmen, 2008). People clearly differ in the degree to which they value different emotions (e.g., Markovitch, Netzer, & Tamir, 2016;Tsai, 2007), and this difference in valuing emotions is likely to lead to differential experience of those emotions (Parker, Majid, Stewart, & Ahrens, 2017).…”
Section: ) Assessment Of Virtue Needs To Consider Within-person Dynamentioning
confidence: 99%